ANALYSIS OF FACTORS THAT CAN INCREASE REPURCHASE INTENTION, WOM AND SITE REVISIT In E-COMMERCE APPLICATIONS - Gilang Pratama Hafidz; Dosman T Sitorus (Jurnal Ekonomi, 2023)
About 90% of internet users in Indonesia have made online transactions, which makes Indonesia the highest level of e-commerce usage worldwide. The purpose of this study is to determine the effect of Web Design, Customer Service, Security and Fulfillment of Needs on the Overall Quality of Electronic Services. Overall Electronic Service Quality on Customer Satisfaction and Customer Trust. To find out the role of Customer Satisfaction and Customer Trust in mediating Repurchase Intention, WOM and Site Revisit in e-commerce applications. 330 people were selected as respondents with the criteria of being at least 17 years old, having made a transaction at least 1 time and being in the JABODETABEK area and then processed using Structural Equation Modeling (SEM). The results show that the Overall Electronic Service Quality has the most impact on customer satisfaction and customer trust. For an indirect effect, Customer Trust mediates the relationship between Overall Electronic Service Quality and Repurchase Intention. Customer satisfaction mediates the relationship between Overall Electronic Service Quality and site revisit. This research provides advice to companies to always improve the Overall Electronic Service Quality in e-commerce to increase Repurchase Intentions. For further research, the researchers can expand the research in terms of broader demographic locations in Indonesia